The teaching of the Art and Science of Medicine - Cokkinos, Dennis V. (DELTOS, 2024)
Teaching of medicine hails back to the age of Hippocrates; in the “Oath” he considers his teachers equal to his parents. Teaching, clinical practice and research constitute the three pillars of medicine, and they are interconnected. The methods of teaching medicine are very important. Auditorium lectures are being replaced by teaching in small groups and problem-oriented teaching. Still the enthusiasm of the teacher who can also become a mentor is a critical ingredient. The teacher should not just transmit but also create knowledge. The advent of artificial intelligence provides new auxiliary tools but also poses new challenges. We must not forget that we are shaping the future of tomorrow.